BEYOND DIGITAL ADOPTION: A THEMATIC ANALYSIS OF EFL TEACHERS’ CHALLENGES IN TECHNOLOGY INTEGRATION - Anwar Fadila; Nita Sitta Rachma; Sheren Dwi Oktaria; Ajeng Nike Setya Diningrum; Dita Lutfiah Puspa Dewi (JETA (Journal of English Teaching and Applied Linguistic), 2026)
The incorporation of digital technology into English as a Foreign Language (EFL) education has been increasingly emphasised, but few studies have critically examined how teachers confront problems in sustaining technology-enhanced classroom practices in everyday teaching realities. This study explores the challenges faced by EFL teachers in integrating digital technology into English courses at secondary schools in Indonesia. The research was conducted qualitatively and exploratively with three English teachers from three distinct senior high schools in Bandar Lampung, Indonesia. Data was acquired through semi-structured interviews, classroom observations and document analysis. Data were analysed using Braun and Clarke’s reflexive thematic analysis. The findings reveal four interrelated themes: persistent infrastructural instability hinders technology-integrated teaching; teachers face pedagogical and emotional challenges in digital teaching; technology integration demands ongoing adaptation and improvisation; and institutional support is uneven and insufficient. The findings indicate that technology integration is not a smooth and linear process but a negotiated pedagogical practice affected by infrastructural restrictions, student involvement concerns, institutional constraints and teachers’ adaptive methods. The study foregrounds the significance of moving beyond the narratives of technology adoption to a more critical understanding of the lived realities of digital education in EFL environments. The report suggests improved infrastructural support, context-sensitive professional development and durable institutional policies to facilitate meaningful technology integration in ELT.